Contribution to the geology of coal deposits in the Zreče area and reflectance-based ranking of its coals - Hamrla, Milan (Geologija, 1987)
The succession of sedimentary strata in the Zreče area, which is situated on the Southern slopes of the Pohorje mountain in NW Yugoslavia, comprises also the Upper Cretaceous Gosau beds and their Tertiary cover. Several thin seams of high volatile bituminous coals are included within the Cretaceous as well as the lower part of the Tertiary sequence. Modest coalfields, exploited in the past, are now of no economic importance. In this paper are described the Tertiary beds at the Zreče site. Their controversial age has recently been considered entirely as Neogene. The interpretation of vitrinite reflectance of the Zreče coals - supposedly chronostratigraphically significant - has been conducive to the hypothesis that freshwater beds of Paleogene age might exist within the preserved Tertiary sequence. The overlying beds comprise coal of much lower rank and belong to the Neogene. A reconstruction attempt of a probable sedimentation and burial history of the Zreče Tertiary succession, considering the alpine tectonic and magmatic events, suggests low paleogeothermal gradients during the Paleogene times and thermal influence of the Rupelian and possibly also Karpatian magmatism in coalification of coals. Some outcrops of the Eocene beds and widespread pebbles of the Eocene rocks in Carynthia and northem Slovenia would conjecture quite an extensive sedimentation area of that time.